Neisseria meningitidis lacking the major porins PorA and PorB are viable and modulate apoptosis and the oxidative burst of neutrophils - Peak, Ian R. (J Proteome Res, 2016)
The bacterial pathogen Neisseria meningitidis expresses two major outer-membrane porins. PorA expression is subject to phase-variation (high frequency, random, on-off switching) and both PorA and PorB are antigenically variable between strains. PorA expression is variable and not correlated with meningococcal colonisation or invasive disease, whereas all naturally-occurring strains express PorB suggesting strong selection for expression. We have generated N. meningitidis strains lacking expression of both major porins, demonstrating that they are dispensable for bacterial growth in vitro. The porAB mutant strain has an exponential growth rate similar to the parental strain, as do the single porA or porB mutants, but the porAB mutant strain does not reach the same cell density in stationary phase. Proteomic analysis suggests that the double mutant strain exhibits compensatory expression changes in proteins associated with cellular redox state, energy/nutrient metabolism, and membrane stability. On solid media, there is obvious growth impairment that is rescued by addition of blood or serum from mammalian species, particularly heme. These porin mutants are not impaired in their capacity to inhibit both staurosporine-induced apoptosis and a phorbol 12-myristate 13-acetate -induced oxidative burst in human neutrophils suggesting that the porins are not the only bacterial factors that can modulate these processes in host cells.